Genetically controlled mtDNA deletions prevent ROS damage by arresting oxidative phosphorylation - Simon Stenberg; Jing Li; Arne B Gjuvsland; Karl Persson; Erik Demitz-Helin; Carles González Peña; Jia-Xing Yue; Ciaran Gilchrist; Timmy Ärengård; Payam Ghiaci; Lisa Larsson-Berglund; Martin Zackrisson; et al. (eLife, 2022)
Deletion of mitochondrial DNA in eukaryotes is currently attributed to rare accidental events associated with mitochondrial replication or repair of double-strand breaks. We report the discovery that yeast cells arrest harmful intramitochondrial superoxide production by shutting down respiration through genetically controlled deletion of mitochondrial oxidative phosphorylation genes. We show that this process critically involves the antioxidant enzyme superoxide dismutase 2 and two-way mitochondrial-nuclear communication through Rtg2 and Rtg3. While mitochondrial DNA homeostasis is rapidly restored after cessation of a short-term superoxide stress, long-term stress causes maladaptive persistence of the deletion process, leading to complete annihilation of the cellular pool of intact mitochondrial genomes and irrevocable loss of respiratory ability. This shows that oxidative stress-induced mitochondrial impairment may be under strict regulatory control. If the results extend to human cells, the results may prove to be of etiological as well as therapeutic importance with regard to age-related mitochondrial impairment and disease.